Analyzing Implicatures in Taliwang Dialect - Ismiati Ismiati (Journal of Languages and Language Teaching, 2021)
This study aims to analyze the types of implicature and flouting maxims and the reasons for doing the flouting in Taliwang Dialect. It applied the descriptive method with a qualitative approach. Data was collected by recording natural conversations among the natives of Taliwang Dialect. It was found two types of implicature, namely, Generalized Conversational Implicature (GCI) and Particularized Conversational Implicatures (PCI). In GCI, the speaker and interlocutor could easily understand the conveyed utterances because they mostly used general statements which are commonly spoken in the Taliwang dialect. In PCI, both speaker and the interlocutor needed a particular knowledge to understand each other because of the flouting maxim. Some speakers or hearers in PCI often break the maxim in a conversation due to some reasons such as accepting untrue or lie information, receiving more information than the needed information, getting irrelevant information and having unclear or ambiguous information.